Juridical Framework of Tertiary Irrigation Networks in Enhancing Food Security - Pipih Ludia Karsa; Ade Marpudin (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2023)
Concerns have arisen within the country over the changing functions of land, particularly the shift from agricultural to non-agricultural use. This transformation carries the risk of land fertility degradation, leading to a decline in the productivity of agricultural staples like rice. Efforts to enhance rice farming productivity, including measures such as irrigation, are instrumental in addressing this issue. The Community Partnership Program aims to formulate strategies for the development and utilization of tertiary irrigation networks that support food security. It employs a Community Education method, providing information, socialization, and counseling on the Utilization and Development of Tertiary Irrigation Networks within the legal framework. This approach seeks to enhance community knowledge and comprehension through engagement with local sub-district officials. The analysis of this data aims to assess the potential for utilizing and developing Tertiary Irrigation Networks, particularly with regard to the jurisdiction of regional authorities responsible for irrigation. Law Number 17 of 2019 concerning Water Resources holds particular relevance to the promotion of agricultural production, particularly rice, which is a priority for both the central and local governments. Effective irrigation networks are pivotal in increasing agricultural productivity, and their utilization and development fall under the purview of local government entities or network managers. Legislative measures may be necessary to define the role of local governments in this context.